Induction of maturational events in gonads of Labeo rohita in response to pituitary extract and ovaprim treatment - Ram, R N; Singh, D M; Singh, I J; Singh, U P (Indian Journal of Fisheries, 2011)
The present study embodies the investigations on sequential histophysiologicalchanges taking place in ovary and testis of L. rohita after inducement by pituitaryextract (PE) and ovaprim (OPm) during spawning phase of its reproductivecycle. In specimens treated with pituitary extract, only fully-grown yolky oocyteswere found to undergo maturational events. In ovaprim treated fish, the oocytespassing through the growth phase were also induced to enter the maturationalphase in subsequent succession to fully-grown yolky oocytes. Observation onmaturational events included germinal vesicle migration (GVM), germinalvesicle breakdown (GVBD) and micropyle formation. Corresponding withovarian histology, the significant change in percentage of oocytes passing throughvarious stages of development was also recorded at 4 and 8 hrs of interval afterPE and OPm injections. At both intervals, the percentage of fully mature stage-VI oocytes with GVBD and follicular wall separation was significantly high inOPm groups compared to PB groups. Moreover, within the groups also, there wassignificant enhancement in the percentage of stage-VI oocytes in time - dependentmanner. In males, pituitary extract could activate only spermatocyte formationand spermiogenesis whereas ovaprim induced advancement in all stages ofspermatogenesis right from spermatogonial proliferation to spermiogenesis resultingin increased level of spermatozoa in testicular lobules. Other characteristicsrelated to gamete quality including percentage at gonadal water contentwere also observed to be of superior order in ovaprim treated fish. These resultssuggest that pituitary preparation is capable of inducing terminal events ingametic maturation faster than ovaprim, whereas the activation of events relatedto sustainability in quality gametic production was of greater magnitudein response to ovaprim resulting in successful synchronization and breeding performancein this species.